Fast and sensitive supercritical fluid chromatography - tandem mass spectrometry multi-class screening method for the determination of doping agents in urine - Nováková, Lucie; Desfontaine, Vincent; Ponzetto, Federico; Nicoli, Raul; Saugy, Martial; Veuthey, Jean-Luc; Guillarme, Davy (Analytica chimica acta, 2016)
This study shows the possibility offered by modern ultra-high performance supercritical fluid chromatography combined with tandem mass spectrometry in doping control analysis. A high throughput screening method was developed for 100 substances belonging to the challenging classes of anabolic agents, hormones and metabolic modulators, synthetic cannabinoids and glucocorticoids, which should be detected at low concentrations in urine. To selectively extract these doping agents from urine, a supported liquid extraction procedure was implemented in a 48-well plate format. At the tested concentration levels ranging from 0.5 to 5 ng/mL, the recoveries were better than 70% for 48-68% of the compounds and higher than 50% for 83-87% of the tested substances. Due to the numerous interferences related to isomers of steroids and ions produced by the loss of water in the electrospray source, the choice of SFC separation conditions was very challenging. After careful optimization, a Diol stationary phase was employed. The total analysis time for the screening assay was only 8 min, and interferences as well as susceptibility to matrix effect (ME) were minimized. With the developed method, about 70% of the compounds had relative ME within the range ±20%, at a concentration of 1 and 5 ng/mL. Finally, limits of detection achieved with the above-described strategy including 5-fold preconcentration were below 0.1 ng/mL for the majority of the tested compounds. Therefore, LODs were systematically better than the minimum required performance levels established by the World anti-doping agency, except for very few metabolites.
Keywords: Limit of Detection; Doping agents; limita detekce; Tandem Mass Spectrometry; Supported liquid extraction; kanabinoidy; Glucocorticoids; Anabolic Agents; Doping in Sports; Supercritical fluid chromatography; superkritická fluidní chromatografie; tandemová hmotnostní spektrometrie; anabolika; Urine; glukokortikoidy; Cannabinoids; Tandem mass spectrometry; doping ve sportu; Chromatography, Supercritical Fluid; Steroids